Binder and preparation method thereof, silicon-based negative pole piece and lithium ion battery
By using binders prepared by free radical polymerization reaction of plant polyphenols and polymers in lithium-ion batteries, the problem of silicon-based anode material being subjected to mechanical stress due to volume expansion during charging and discharging is solved, and better Structural stability and cycle life.
Patent Information
- Application Number
- CN202411615566.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
In existing lithium-ion batteries, the silicon-based negative electrode material is subjected to mechanical stress due to volume expansion during charging and discharging, resulting in material powdering, reducing battery stability and cycle life.
A binder prepared by a free radical polymerization reaction of plant polyphenols and polymers is used. The polymerization unit of the binder has an end capping group. By undergoing free radical polymerization with the hydroxyl group in the plant polyphenol, a branched structure is formed. Strengthen the mechanical strength of the binder.
It effectively solves the problem of easy movement of the adhesive under high mechanical stress and insufficient adhesion, and improves the structural stability and cycle life of the silicon-based negative electrode sheet.
Smart Images

Figure CN119517988A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a binder for lithium ion batteries, a silicon-based negative electrode plate, a lithium ion battery and a method for preparing the binder for lithium ion batteries. Background Art
[0002] Lithium-ion batteries have become the best choice for people due to their advantages such as long life, flexible design and portability. The theoretical capacity of silicon materials is more than 10 times that of traditional graphite. Silicon materials as the negative electrode of the new generation of lithium-ion batteries have attracted much attention and expectations. However, the silicon negative electrode has a huge volume expansion during the charging and discharging process. As the volume of silicon changes, the silicon active material will be subjected to high mechanical stress, which will cause the silicon material itself to pulverize. As the silicon material pulverizes, the stability of the battery will decrease and the cycle life of the battery will be shortened.
[0003] The binder in the battery is a key material. The main function of the binder is to bond the active material, conductive agent and current collector to maintain the stability of the electrode structure, ensure a complete conductive network, and enable the normal operation of the lithium-ion battery.
[0004] At present, the binders commonly used in silicon-based negative electrode materials include sodium alginate (Alg), sodium carboxymethyl cellulose, polyacrylic acid (PAA), etc. These binders all contain polar groups, such as carboxyl (-COOH) or its sodium salt form (-COONa). These polar groups can form hydrogen bonds or ionic bonds with functional groups on the surface of negative electrode materials (such as graphite, silicon-based materials or other conductive compounds), thereby producing a bonding effect. However, the linear chain structure of these binders makes it easy for them to move on the silicon surface under high mechanical stress. This means that when the volume of the electrode material changes, these binders may not be able to provide sufficient mechanical strength to adapt to these changes, resulting in the destruction of the electrode structure.
[0005] The prior art has improved these binders, for example, by adding branches to the above binders to form a claw-like structure binder, so that it can be riveted to the negative electrode to reduce the risk of movement. However, due to the limitation that the main chain of the above binder is a linear structure, for example, the main chain of polyacrylic acid is acrylic acid, it is impossible to add more branches. The reason is that once more branches are added, the isomerization steric hindrance between the branches is too small, so that agglomeration and adhesion occur inside, and it is impossible to achieve bonding with the negative electrode by riveting, and it is impossible to protect the negative electrode. Based on this, it is necessary to study the binder to solve the above technical problems.
[0006] The present invention provides the following technical solutions to solve the above technical problems.
[0007] The present invention provides a binder for lithium ion batteries. The binder is obtained by free radical polymerization of plant polyphenols and polymers. The polymers include polymerization units, the polymerization units have end-capping groups, and the polymerization units have a structure shown in general formula (I). The hydroxyl groups in the plant polyphenols and the end-capping groups in the polymers undergo free radical polymerization.
[0008]
[0009] Among them, * represents the bonding position between polymer units, R 1 Selected from -CH 3 、-NH 2 、-CH 2 CH 2 O.
[0010] -CH 3 (CH 2 ) 3 、-CH 2 CH(CH 3 ) 2 、-CH 2 CHOCH 3 、-CH 2 CH 3 、-CH 2 CHCH 3 , polyvinyl alcohol or fatty alcohol.
[0011] The above technical solution can effectively solve the problem that the adhesive is easy to move on the silicon surface under high mechanical stress and has insufficient adhesion.
[0012] Optionally, the polymerized unit includes polymerized unit a, polymerized unit b, polymerized unit c and polymerized unit d, the polymerized unit a has a structural formula of formula (II), the polymerized unit b has a structural formula of formula (III), the polymerized unit c has a structural formula of formula (IV), the polymerized unit d has a structural formula of formula (V),
[0013]
[0014]
[0015] Wherein, in formula (II) to formula (V), * represents the bonding position between polymer units, R 2 Selected from -OH, -NH 2 、-B(OH) 2 、-CN、-SO 3 M, -PO 3 HM, -PO 3 M 2 or -COOM, M is selected from Li + Or Na+ .
[0016] Optionally, the polymer is obtained by RAFT controlled radical polymerization of polymerized units a, b, c and d, and the polymer includes a polymer represented by formula (VI);
[0017]
[0018] R 2 Selected from -OH, -NH 2 、-B(OH) 2 、-CN、-SO 3 M, -PO 3 HM, -PO 3 M 2 or -COOM, wherein M is selected from Li + Or Na + , wherein * represents the bonding position between polymer units, i, j, k or l are each independently i=1-10, j=1-10, k=1-10, l=1-10, and n=6-15.
[0019] Optionally, the plant polyphenol is tara gum.
[0020] Optionally, the binder is a product obtained by free radical polymerization of a polymer and alcoholic hydroxyl groups on tara gum hydroxymethyl alcohol.
[0021] The present invention also provides a silicon-based negative electrode plate, comprising the binder in any of the above embodiments.
[0022] By adopting the above technical solution, the silicon-based negative electrode plate has good structural stability and long cycle life.
[0023] The present invention also provides a lithium ion battery, which comprises the binder in any one of the above embodiments.
[0024] By adopting the above technical solution, the battery has good structural stability and long cycle life.
[0025] The present invention also provides a method for preparing the binder in any of the above embodiments, the method comprising the steps of:
[0026] Preparation of polymer: dissolving a chain transfer agent, an initiator and a monomer for forming a polymer in a solvent to carry out a chain polymerization reaction to obtain a polymer, wherein an inert gas is always introduced during the reaction;
[0027] Preparation of the binder: adding plant polyphenols to a polymer to obtain a mixed solution, and then heating the mixed solution in a water bath to obtain the binder.
[0028] By adopting this technical solution, an adhesive with better adhesion effect can be obtained.
[0029] Optionally, the plant polyphenol is tara gum, and the water bath heating temperature is 70-90°C.
[0030] Optionally, the chain transfer agent is 2-cyano-3-methyl-2-butylbenzodithioate and / or S-(2-cyano-2-propyl)-S-dodecyltrithiocarbonyl ester, and the initiator is azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO).
[0031] Optionally, after the step of preparing the binder, a neutralization reaction step is further included, wherein the neutralization reaction step is: adding a solution containing Na + or Li + of alkaline solution. DETAILED DESCRIPTION
[0032] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0033] The term "plant polyphenols" is also often referred to as plant phenolic compounds, which are a class of natural compounds with a polyphenol structure that are widely present in plants. Polyphenolic compounds usually have a benzene ring or a polycyclic ring (such as a six-membered ring) as a basic structural unit, with one or more hydroxyl groups (-OH) as substituents on the benzene ring or the polycyclic ring. The types of plant polyphenols are very diverse, such as flavonoids, tannins (such as tannic acid), lignin, tara gum, etc.
[0034] The term "end-capping group" in the present invention refers to a specific chemical group at both ends of a polymer chain, such as a hydrogen atom or a halogen atom.
[0035] The term "polyvinyl alcohol" (PVA) is a synthetic polymer compound formed by polymerization of vinyl alcohol units. The chemical formula of polyvinyl alcohol is [-CH 2 -CHOH-]n, where n represents the degree of polymerization, that is, the number of monomer repeating units.
[0036] The term "fatty alcohol" refers to a class of alcohol compounds with long-chain alkyl groups and hydroxyl (-OH) functional groups. They are usually obtained by reduction of long-chain fatty acids or synthesized by alkylation reactions. The general formula of fatty alcohol is CnH 2n+1 OH, where n represents the number of carbon atoms in the alkyl chain, which is usually between 8 and 36, but can be more.
[0037] If not otherwise specified, in this application, polymer refers to the product formed by monomer polymerization, often including many polymer aggregates, each polymer is formed by many simple polymerization units repeatedly connected by covalent bonds, and the monomer is a compound of synthetic polymer. Polymer can include homopolymer, copolymer, prepolymer, etc., and is not limited to this. Homopolymer refers to a polymer polymerized by a monomer. Copolymer refers to a polymer polymerized by two or more monomers. Copolymer includes random copolymer (structure is such as -AABABBBAAABBA-), alternating copolymer (structure is such as -ABABABAB-), graft copolymer (structure is such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymer (structure is such as -AAAAA-BBBBBB-AAAAA-) etc.
[0039] The present invention provides a polymer, which includes a polymer unit, and the polymer unit has a structure shown in the general formula (I). According to the structure, the present invention introduces a branch with a specific function on the main chain of a polymer such as polyacrylate, thereby obtaining a claw-like structure, so that it can be bonded to the negative electrode by riveting. However, due to the limitation that the main chain of polyacrylate is a linear chain, if more branches are added, the distance between the branches will be smaller, and there will be a greater attraction between the branches, which will reduce the isomeric steric hindrance between the branches, so that agglomeration and adhesion will occur inside. Therefore, it is not advisable to add more branches, which will result in the inability to form more claw-like structures. In this context, if a polymer such as polyacrylate (claw-like structure) is used directly as a binder, there will still be problems such as easy movement on the silicon surface under high mechanical stress and insufficient adhesion.
[0040] To this end, the present invention uses a polymer (polyacrylate) as a side chain and a plant polyphenol as a main chain, and grafts the side chain onto the plant polyphenol through a free radical polymerization reaction. Specifically, the hydroxyl groups on the benzene ring in the plant polyphenol and the end groups in the polyacrylate undergo a free radical polymerization reaction, so that the polymer can be grafted onto the plant polyphenol as a side chain, thereby solving the problem that the binder is easy to move on the silicon surface under high mechanical stress and the adhesion is insufficient.
[0041]
[0042] Among them, * represents the bonding position between polymer units, R 1 Selected from -CH 3 、-NH 2 、-CH 2 CH 2 O.
[0043] -CH 3 (CH 2 ) 3 、-CH 2 CH(CH 3 ) 2 、-CH 2 CHOCH 3 、-CH 2 CH 3 、-CH 2 CHCH 3 , polyvinyl alcohol or fatty alcohol.
[0044] Specifically, plant polyphenol molecules contain more hydroxyl groups, which can form hydrogen bonds with many substances. For example, in negative electrode materials, polyphenols can be combined with the surface of active substances (such as graphite, silicon, etc.) through hydrogen bonds or van der Waals forces, thereby playing a role in fixing and bonding. In addition, plant polyphenols also contain more benzene rings. The presence of more benzene rings on the one hand increases the distance between groups within the molecule, such as the distance between hydroxyl groups on different benzene rings or on the same benzene ring, thereby making the attraction between groups weaker. In addition, the benzene rings in polyphenols have a conjugated π electron system, which makes the entire molecular structure more rigid. The rigid structure can limit the relative movement of atoms within the molecule, thereby making the isomeric steric hindrance between groups larger, and the spatial structure is not linear, but a three-dimensional network structure, so it effectively avoids the formation of hydrogen bonds between hydroxyl groups within the molecule, and avoids the problems of agglomeration and adhesion. That is to say, when plant polyphenols are used as the main chain and polyacrylates are grafted onto plant polyphenols as branches (polyacrylates are used as branches to replace hydroxyl groups on plant polyphenols), since plant polyphenols have more benzene rings, the isomeric steric hindrance is larger, so the spacing between the branches can be pulled apart, so that the spacing between the branches is larger, thereby making the attraction between the branches smaller, not only is it not easy to have the problem of agglomeration and adhesion, but it can also use the stable rigid structure of plant polyphenols and the characteristics of multiple hydroxyl groups to graft more polyacrylate branches onto plant polyphenols, and the branches can be used as claws, which can achieve better bonding effect by riveting the negative electrode and gluing on the negative electrode. In other words, plant polyphenols will be tightly adsorbed on the surface of the negative electrode material under the action of hydroxyl groups, and the branch chain is equivalent to a tentacle, which rivets the negative electrode and gluing on the negative electrode to achieve better bonding effect.
[0045] Furthermore, the polymerized unit in the above embodiment can be selected from the structures shown in formula (II) to formula (V), and the polymerized unit includes polymerized unit a, polymerized unit b, polymerized unit c and polymerized unit d, the structural formula of polymerized unit a is formula (II), the structural formula of polymerized unit b is formula (III), the structural formula of polymerized unit c is formula (IV), and the structural formula of polymerized unit d is formula (V).
[0046]
[0047] Wherein, in formula (II) to formula (V), * represents the bonding position between polymer units, R 2 Selected from -OH, -NH 2 、-B(OH) 2 、-CN、-SO 3 M, -PO 3 HM, -PO 3 M 2 or -COOM, M is selected from Li + Or Na + .
[0048] In this embodiment, the polymer units are composed of the above four specific types of polymer units, which can improve the ability to absorb and retain electrolyte and the cycle stability of the battery. Specifically, the side chains of the above polymer units have good affinity with the electrolyte, which makes it possible to improve the ability to absorb and retain electrolyte when applied to the negative electrode of a lithium-ion battery, thereby significantly slowing down the electrochemical capacity decay of the lithium-ion battery. In addition, it also has a better regulating effect. The multi-stage polymer can better adjust the hydrophilicity and lipophilicity of the overall polymer through the HLB values of different monomers, so that the performance can be adjusted more accurately.
[0049] Further, the polymer units a, b, c and d are obtained by RAFT controlled radical polymerization, and the polymer includes a polymer of formula (VI);
[0050]
[0051] R 2 Selected from -OH, -NH 2 、-B(OH) 2 、-CN、-SO 3 M, -PO 3 HM, -PO 3 M 2 or -COOM, wherein M is selected from Li + Or Na +. Wherein, * represents the bonding position between polymerized units, i, j, k or l are each independently i=1-10, j=1-10, k=1-10, l=1-10, and n=6-15. Wherein, i, j, k or l represents the molar ratio of polymerized monomers (for example, i represents the molar ratio of polymerized unit a); in addition, each i, j, k or l may be the same or different, and each i, j, k or l is, for example but not limited to, i=1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; j=1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; k=1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; l=1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; n=6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.
[0052] It should be noted that the symbol "\\" indicates the structure of the omitted polymerization unit, for example, the omitted polymerization unit is any one or more of polymerization unit a, polymerization unit b, polymerization unit c or polymerization unit d. This arrangement can make the molecular weight of the binder within a suitable range, thereby obtaining a better bonding effect. Furthermore, i:j:k:l=10:4:5:1.
[0053] The above formula (VI) merely exemplifies that the polymer has i, j, k, and l polymerization units, and does not limit the specific bonding order of each polymerization unit. In other words, each polymerization unit can be bonded in various forms, including but not limited to random bonding, alternating bonding, or block bonding.
[0054] Furthermore, in each of the above embodiments, the plant polyphenol is tara gum. The structure of tara gum is shown in formula (VII).
[0055]
[0056] According to the above structure, the hydroxyl group in Tara gum includes the alcoholic hydroxyl group on hydroxymethyl alcohol and the alcoholic hydroxyl group on the six-membered ring. Due to the high activity of the alcoholic hydroxyl group on the hydroxymethyl alcohol, the alcoholic hydroxyl group on the six-membered ring forms a π bond on the ring, so at a certain temperature, the alcoholic hydroxyl group on the hydroxymethyl alcohol is more likely to fall off to form a free radical, and then under the action of the free radical, it reacts with polyacrylate to generate a binder. Tara gum has more hydroxyl groups, and has a small molecular weight (tens of thousands of molecular weight), and the advantage of low viscosity, so Tara gum is selected as the main chain, which is convenient to control the molecular weight of the final binder and make it within a suitable range.
[0057] Further, the binder is a product obtained by free radical polymerization of the polymer and the alcoholic hydroxyl groups on the hydroxymethyl alcohol of tara gum. The reason is that if the polymer and the alcoholic hydroxyl groups on the hexacyclic ring of tara gum undergo free radical polymerization, the isomerization internal resistance will be reduced, thereby increasing the attraction between the groups, causing the polymer to have internal agglomeration and adhesion problems, and it is also impossible to use it as a binder to achieve good viscosity with the negative electrode material. Therefore, a better way is that the polymer undergoes free radical polymerization with the alcoholic hydroxyl groups on the hydroxymethyl alcohol of tara gum, thereby utilizing the steric effect of tara gum itself, so that the polymer side chains are not easy to produce adhesion, but to adhere to the negative electrode material.
[0058] The present invention also provides a silicon-based negative electrode plate, comprising the binder in any of the above embodiments.
[0059] By adopting the above technical solution, the silicon-based negative electrode plate has good structural stability and long cycle life.
[0060] The present invention also provides a lithium ion battery, comprising the binder in any one of the above embodiments.
[0061] By adopting the above technical solution, the electrode has good structural stability and long cycle life.
[0062] The present invention also provides a method for preparing the above-mentioned binder, which comprises the steps of:
[0063] Preparation of polymer: dissolving a chain transfer agent, an initiator and a monomer for forming a polymer in a solvent to carry out a chain polymerization reaction (RAFT free radical polymerization reaction) to obtain a polymer, wherein an inert gas is always introduced during the reaction;
[0064] Preparation of the binder: adding plant polyphenols to a polymer to obtain a mixed solution, and then heating the mixed solution in a water bath to obtain the binder.
[0065] Specifically, primary free radicals are generated by free radical initiators, which can attack monomer molecules to form a new free radical, i.e., a propagating free radical (free radical monomer). Under the action of a chain transfer agent, the free radical monomer continues to attack the monomer molecules and continuously polymerizes to obtain a polymer. Since oxygen is a free radical scavenger, it can react with free radicals, resulting in the termination of the polymerization chain. Therefore, an inert gas is always introduced during the reaction process. The introduced inert gas can remove oxygen from the system and prevent the free radicals from being consumed by oxygen, thereby ensuring the continuation of the polymerization reaction.
[0066] Furthermore, the plant polyphenol is tara gum, and the water bath heating temperature is 70-90° C. Under this temperature condition, the alcoholic hydroxyl groups on the hydroxymethyl alcohol in the tara gum can be detached, while the alcoholic hydroxyl groups on the six-membered ring can not be detached, so that the obtained binder can be ensured to be a product obtained by free radical polymerization reaction between the polymer and the alcoholic hydroxyl groups on the hydroxymethyl alcohol of the tara gum, so that a better adhesion effect can be obtained.
[0067] Further, the chain transfer agent is 2-cyano-3-methyl-2-butylbenzodithioester and / or S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester. Thus, the molecular weight of the polymer can be effectively controlled to have a narrower molecular weight distribution, and the rate of free radical polymerization reaction can be increased, that is, the rate of polymer generation can be increased. In particular, the chain transfer agent is S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester.
[0068] Further, the initiator is azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO). In particular, the initiator is azobisisobutyronitrile (AIBN). This can increase the rate of the free radical polymerization reaction.
[0069] Furthermore, after the step of preparing the binder, a neutralization reaction step is further included, wherein the neutralization reaction step is: adding a mixture containing Na + or Li + alkaline solution. Since the existing binders are prepared based on acidic resins (such as polyacrylic acid resins), a neutralization reaction is required to adjust the pH value of the binder after the manufacturing is completed due to the strong pickling, so that it can be better used as a negative electrode of the battery. Since the plant polyphenols in the present invention have more hydroxyl groups, the hydrogen in the hydroxyl groups is ionized after the neutralization reaction and replaced by sodium ions or lithium ions, thereby increasing the shuttle rate of lithium ions, thereby improving the charge and discharge efficiency. Specifically, after the polymer binder is prepared, since its pH value is in the strong acid range, LiOH and NaHCO 3 The alkaline substance undergoes a neutralization reaction to adjust the pH of the polymer to around pH=7, and the pH of the binder is finally weakly alkaline. The specific reaction process is as follows:
[0070]
[0071] The present invention is further described in detail below through specific examples and comparative examples (it should be noted that 2% glue solution means that the mass fraction of CMC in the glue solution is 2%, 40% solid content means that the mass percentage of solid SBR in the glue solution is 40%, M represents molar concentration, 1M means the molar concentration is 1Mol / L, for example, 1M LiPF 6 It means that each liter of solution contains 1 mole of lithium salt lithium hexafluorophosphate (LiPF6 ).
[0072] Example 1
[0073] Pretreatment: Tara gum is purified with anhydrous ethanol to obtain a colloid-like substance, and then the ethanol is removed using a rotary evaporator to obtain pure Tara gum;
[0074] Preparation of polymer: Add monomers methyl methacrylate (1 g), polyethylene glycol methacrylate (Mn≈300-1000) (0.4 g), 2-isooctanoic acid methyl acrylate (0.5 g), and 3-sulfopropyl methacrylate (0.1 g) into a three-necked flask and stir for 1 h to obtain solution A. Then take 1.71×10 -4 g S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester and 2.2×10 -5 g azobisisobutyronitrile (AIBN) and dissolved in 5 g DMF, cooled in an ice bath and dissolved by ultrasonication, and then dripped into the above solution A to obtain a polymer, wherein the dripping rate was controlled at 5 mL / min, and nitrogen was introduced as a protective gas during the reaction;
[0075] Preparation of binder: Take 4g of pure tara gum and 150g of DMF (solvent), add the two into a 250mL four-necked flask, stir at room temperature for 5h to fully dissolve it to obtain solution B. Then add solution B to the polymer, place it in a 45℃ water bath to react for 12h after the dropwise addition. After the reaction is completed, take out the reaction solution, add 500mL of anhydrous ethanol to precipitate the solid, and wash the obtained solid product with anhydrous ethanol several times and then vacuum dry it. The vacuum drying temperature is 50℃ and the drying time is 12h. The obtained solid product is the binder.
[0076] Application Example 1
[0077] Take graphite, conductive agent, CMC (2% glue) and binder (binder in Example 1) with a mass percentage of 95.8:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 55%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0078] Application Example 2
[0079] Take graphite, silicon dioxide, conductive agent, CMC (2% glue) and binder (binder in Example 1) with a mass percentage of 89.09:6.71:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1MLiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test structure is shown in Table 1.
[0080] Application Example 3
[0081] Take graphite, silicon carbon powder, conductive agent, CMC (2% glue) and binder (binder in Example 1) with a mass percentage of 90.53:5.27:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1MLiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0082] Application Comparative Example 1
[0083] Disperse graphite, conductive agent, CMC (2% glue solution), and SBR (40% solid content) in a mass ratio of 95.8:1.5:1.2:1.5 into appropriate deionized water, keep the solid content at 55%, and stir for 12 hours. Evenly coat the mixed slurry on copper foil and dry it at 80°C under vacuum for 12 hours to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and assembled into a 2032 button battery with a lithium sheet as the counter electrode, in which the electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0084] Application Comparative Example 2
[0085] Take graphite, silicon dioxide, conductive agent, CMC (2% glue), SBR (40% solid content) with a mass percentage of 89.09:6.71:1.5:1.2:1.5 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on the copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0086] Application Comparative Example 3
[0087] Take graphite, silicon carbon powder, conductive agent, CMC (2% glue) and SBR (40% solid content) with a mass percentage of 90.53:5.27:1.5:1.2:1.5 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on the copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0088] Application Comparative Example 4
[0089] Take graphite, conductive agent, CMC (2% glue solution), and tara gum with a mass percentage of 95.8:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 55%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery, in which the electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0090] Application Comparative Example 5
[0091] Take graphite, silicon dioxide, conductive agent, CMC (2% glue solution) and tara gum with a mass percentage of 89.09:6.71:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery. The electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0092] Application Comparative Example 6
[0093] Take graphite, silicon carbon powder, conductive agent, CMC (2% glue solution) and tara gum with a mass percentage of 90.53:5.27:1.5:0.5:2.2 and disperse them in appropriate deionized water, keep the solid content at 52%, and stir for 12 hours. The mixed slurry is evenly coated on copper foil and dried at 80°C for 12 hours under vacuum conditions to obtain the negative electrode. After drying, the electrode is cut and transferred to the glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button battery. The electrolyte is 1M LiPF 6 The electrolyte is a PC / EC (volume ratio 1:1) solution containing 3% FEC additive. Finally, the button cell is subjected to constant current charge and discharge test. The test results are shown in Table 1.
[0094] Among them, the first cycle coulombic efficiency = first discharge capacity / first charge capacity; the capacity retention rate refers to the ability of the battery to maintain its initial capacity after multiple charge and discharge cycles during the charge and discharge cycle process. For example, the 800-cycle capacity retention rate refers to the ability of the battery to maintain its initial capacity after 800 charge and discharge cycles during the charge and discharge cycle process.
[0095] Table 1
[0096]
[0097] By comparing Application Comparison Example 1, Application Comparison Example 4 and Application Example 1, in which the negative electrodes are all graphite, it can be seen that the binder has no improvement effect on the capacity retention rate.
[0098] Comparison of Application Comparative Example 2, Application Comparative Example 5 and Application Example 2, in which the negative electrodes are all silicon monoxide, shows that the use of the binder provided by the present invention can significantly improve the first cycle coulombic efficiency and capacity retention rate. Analysis of the reasons shows that the binder of the present invention uses tara gum as the main chain and polypropionate polymer as the side chain, so that the binder can firmly adhere the active material to the current collector, ensuring the stability of the electrode structure during the charge and discharge process, so that during the cycle, the binder can effectively buffer the volume change of the silicon negative electrode and improve the capacity retention rate.
[0099] Comparison of Application Comparative Example 3, Application Comparative Example 6 and Application Example 3, in which the negative electrodes are all silicon carbon, shows that the use of the binder provided by the present invention can significantly improve the capacity retention rate. Analysis of the reasons shows that the binder of the present invention uses tara gum as the main chain and polypropionate polymer as the side chain, so that the binder can firmly adhere the active material to the current collector, ensuring the stability of the electrode structure during the charge and discharge process, so that during the cycle, the binder can effectively buffer the volume change of the silicon negative electrode and improve the capacity retention rate.
[0100] In summary, the binder provided by the present invention is more suitable for use in silicon negative electrodes, and can significantly improve the capacity retention rate and increase the service life.
[0101] Although the present invention has been described by reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A binder for lithium ion batteries, characterized in that: The binder is obtained by free radical polymerization of plant polyphenols and polymers, wherein the polymer comprises a polymerization unit, the polymerization unit has an end-capping group, and the polymerization unit has a structure represented by general formula (I), wherein the hydroxyl group in the plant polyphenols and the end-capping group in the polymer undergo the free radical polymerization reaction; Wherein, * represents the bonding position between polymer units, and R1 is selected from one of -CH3, -NH2, -CH2CH2O, -CH3(CH2)3, -CH2CH(CH3)2, -CH2CHOCH3, -CH2CH3, -CH2CHCH3, polyvinyl alcohol or fatty alcohol.
2. The adhesive according to claim 1, characterized in that The polymerized unit comprises a polymerized unit a, a polymerized unit b, a polymerized unit c and a polymerized unit d, wherein the polymerized unit a has a structural formula of formula (II), the polymerized unit b has a structural formula of formula (III), the polymerized unit c has a structural formula of (IV), and the polymerized unit d has a structural formula of formula (V), Wherein, in formula (II) to formula (V), * represents the bonding position between polymer units, R2 is selected from one of -OH, -NH2, -B(OH)2, -CN, -SO3M, -PO3HM, -PO3M2 or -COOM, and M is selected from Li + 、Na + .
3. The adhesive according to claim 2, characterized in that The polymer is obtained by RAFT controlled free radical polymerization of polymer units a, b, c and d, and the polymer includes a polymer represented by formula (VI); R2 is selected from one of -OH, -NH2, -B(OH)2, -CN, -SO3M, -PO3HM, -PO3M2 or -COOM, wherein M is selected from Li + Or Na + ; Wherein, * represents the bonding position between polymer units, i, j, k or l are each independently i=1-10, j=1-10, k=1-10, l=1-10, and n=6-15.
4. The adhesive according to claim 1, characterized in that The plant polyphenol is tara gum.
5. The binder according to claim 4, wherein the binder is a product obtained by free radical polymerization of a polymer and the alcoholic hydroxyl groups on the tara gum hydroxymethyl alcohol.
6. A silicon-based negative electrode plate, characterized in that: Contains the binder according to any one of claims 1 to 5.
7. A lithium ion battery, characterized in that: Contains the binder according to any one of claims 1 to 5.
8. A method for preparing the adhesive according to any one of claims 1 to 5, characterized in that: Includes steps: Preparation of polymer: dissolving a chain transfer agent, an initiator and a monomer for forming a polymer in a solvent to carry out a chain polymerization reaction to obtain a polymer, wherein an inert gas is always introduced during the reaction; Preparation of the binder: adding plant polyphenols to the polymer to obtain a mixed solution, and then heating the mixed solution in a water bath to obtain the binder.
9. The preparation method according to claim 8, characterized in that: The plant polyphenol is tara gum, and the water bath heating temperature is 70-90°C.
10. The preparation method according to claim 8, characterized in that: The chain transfer agent is 2-cyano-3-methyl-2-butylbenzodithioester and / or S-(2-cyano-2-propyl)-S-dodecyltrithiocarbonyl ester, and the initiator is azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO).
11. The preparation method according to claim 8, characterized in that: The step of preparing the binder further includes a neutralization reaction step, wherein the neutralization reaction step is: adding a mixture containing Na + or Li + of alkaline solution.